Using the Capabilities of the AutoCAD Program to Solve Metric and Position Issues - Zhabbarov, Anvar E.; Akhmedov, Nurali O. (International Journal on Human-Computing Studies, 2024)
The article proposes to “compare” the solution of metric and positional problems in engineering graphics, that is, to perform it in practice with the help of computer programs after doing it manually based on theoretical knowledge. Theoretical knowledge teaches how to read drawings, how to imagine objects spatially depending on their representation, what operations are necessary to solve the problem, and introduces the laws and rules. Computer graphic programs, on the other hand, ensure that the drawings are done quickly, cleanly and accurately.